Stratigraphic Simulation in Sequence Stratigraphy and Basin Analysis - WAN RASHID, WAN EDANI (Universiti Teknologi Petronas, 2008)
Stratigraphic simulation is a modelling technique which can be used for exploration purposes to understand the depositional geometries and architectures of a basin. It is a method where it can simulate realistic stratigraphic attributes using geologically reasonable values of selected process parameters. A study in understanding the evolution of stratal pattern in Malay Basin has been done using this forward simulation. It is to investigate the main factor that controls the sedimentation in the basin. From previous study using overpressure modelling, sedimentation rate has caused the compaction and subsidence in the basin as well controlled the architecture of the Malay Basin. Two dimensional forward modelling (SEDP AK) that developed by the Stratigraphic Modelling Group at the University of South Carolina is used to reconstruct a depositional history of the Malay Basin, in verifying that subsidence plays a major role in the development of the basin. It has been reconstructed with response to changing rates of tectonic movements/subsidence, eustasy and also sediment supply by using present day observed seismic stratigraphic section. The input value for the parameters in this trial-an-error process are manipulated by logic/rules and iteratively corrected until there was an agreement between modelling results and the observed geometries in the seismic cross sections. As a result, the stratal geometries have been created using simulation technique are comparable to the observed data where the most controlling factor of this basin's stratal pattern development is subsidence. This simulation also revealed the differential subsidence produce different system tract because it achieved to demonstrate that reactivation of a normal fault has created an accommodation space for deposition of the lowstand fan system. It is important to understand the controlling factors of sequence development of this basin because enable us to predict possible target play. However, there is limitation in using the program such that is only as good as assumptions that go into it and encompass preconceived concepts and biases of designer.